(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
This article examines the Medieval legend of young Charlemagne’s love experiences and analyzes its evolution through a comparative investigation of its main French and Italian rewritings. In particular, the contribution focuses on the fragments of Mainet and on the first book of Girart d’Amiens’ Istoire le roy Charlemaine, on the Franco-Italian Karleto and on Andrea da Barberino’s Reali di Francia. The latter work also allows us to highlight Andrea’s general adhesion to the Tuscan literary culture of the Middle Ages (especially Stilnovo and novella) and its indebtedness, in both form and content, to the love story of Buovo d’Antona and Drusiana, also included in Andrea’s work.